Preoperative Depressive Symptoms associated with Poor Functional Recovery after Surgery - Tang, Victoria (J Am Geriatr Soc, 2020)
BACKGROUND/OBJECTIVES: Depression screening and treatment for older adults are recommended in Age-Friendly Health Systems. Few studies have evaluated the association between depressive symptoms and post-operative functioning. We aim to determine the association between varying levels of depressive symptoms in the preoperative setting with post-operative functional recovery. DESIGN: Prospective cohort study SETTING: Two academic hospitals in Boston, MA. PARTICIPANTS: Surgical patients aged ≥ 70 years (N=560). MEASUREMENTS: Participants were assessed preoperatively and 1 year post-operatively. Preoperative evaluation included the 15-item short-form Geriatric Depression Scale (GDS). Results were categorized: low (GDS 0–1), moderate (2–5), and high (6–15) symptom burden. Primary outcome was one-year instrumental activities of daily living (IADL) functional decline. Secondary outcomes included hospital stay >5 days, discharge to post-acute care(PAC) facility, readmission within 30 days. RESULTS: Mean participant age was 76.6±5 years, 58% were women, 81% underwent an orthopedic operation, 13% gastrointestinal, 6% vascular; 13% had functional decline at 1 year after their operation (by symptom burden: low – 5.5%, moderate – 14.8%, high – 38.6%). After adjusting for age, gender, and comorbidity, those with moderate or high depressive symptoms demonstrated greater odds of functional decline at 1 year compared to those with a low symptom burden (moderate: adjusted odds ratio [AOR] 2.7, 95%CI 1.3–5.3; high: AOR 9.3, CI 4.2–20.6), discharge to PAC facility (moderate: AOR 1.7, CI 1.2–2.6; high: AOR 2.7, CI 1.4–5.1), but demonstrated no significant association with 30-day readmission or hospital length of stay >5 days. CONCLUSION: Greater burden of preoperative depressive symptoms is associated with increased likelihood of functional decline at 1 year after surgery and of discharge to PAC facility. Preoperative assessment of the burden of depressive symptoms in older adults undergoing elective surgery may be helpful in identifying patients at high risk of poor outcomes.